The impact of frontal and cerebellar lesions on decision making: evidence from the Iowa Gambling Task - Cardoso, Caroline de Oliveira; Branco, Laura Damiani; Cotrena, Charles; Kristensen, Christian Haag; Schneider Bakos, Daniela Di Giorge; Fonseca, Rochele Paz (Frontiers in Neuroscience, 2014)
Although the frontal lobes have traditionally been considered the neural substrates of executive functioning, recent studies have suggested that other structures, such as the cerebellum, may be associated with these abilities. The role of the cerebellum has only been sparsely investigated in connection with decision making (DM), an important component of executive functioning, and the few results obtained on this front have been inconclusive. The current study sought to investigate the role of the cerebellum in DM by comparing the performance of patients withcerebellar strokes, frontal-damaged patients and a healthy control group on the Iowa Gambling Task (IGT). A total of nine cerebellar-damaged adults participated in the study, as well as nine individuals with frontal strokes and 18 control individuals. Patients were administered a version of the IGT adapted to the population of Southern Brazil. There was a marginal difference inmean IGT net scorebetween the two clinical groups, although both displayed impaired performance as compared to the control group. Overall, the DM ability of patients with cerebellar damage proved to be more preserved than that of individuals with frontal lobe strokes, but less preserved than that of the control group. These data suggested that, while the frontal lobes may be the most important brain structures for DM, the cerebellum might also play an active role in this cognitive function. Future studies assessing participants with lesions in different cerebellar regions and hemispheres will prove invaluable for the understanding of the neural structures involved in DM, and make significant contributions to the globalist-localizationist debate in DM neuroscience.